Combined theoretical and experimental investigation of the photodecarboxylation of nitrophenylacetates and its implications for the design of improved ortho-nitrobenzylic caging groups - Mewes, Jan-Michael; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2012)
The photodecarboxylation mechanism of different structural isomers of nitrophenylacetate (NPA) has been investigated using quantum chemical calculations as well as time-resolved UV-pump VIS-probe spectroscopy. It is shown that for a proper theoretical description of the excited states of anionic NPA in aqueous solution a careful consideration of the influence of the solvent is indispensable. In this sense, NPA is an example that demonstrates how character and lifetime of the involved excited states affect the results of equilibrium and nonequilibrium solvation approaches. An ultrafast decay channel via a repulsive singlet state has been found to be responsible for observed ultrafast CO2 release, while another very efficient but slower CO2 release channel is found to proceed via intersystem crossing and subsequent decay via a repulsive triplet state. After all, differences and similarities in the observed excited state dynamics of the isomers are conclusively explained. Most notably, the much smaller quantum yield of CO2 release from the ortho-isomer is due to an alternative excited-state hydrogen-transfer channel, which occurs along a triplet and singlet pathway. On the basis of theoretical and experimental evidence suggesting that the multiplicity of the route taken determines the photoproduct yield, we provide guidelines for the design of ortho-nitrobenzylic caging groups with improved uncaging yield.